Cognitive Behavior Therapy Group Counseling for Reducing Work Stress - Saman, Abdul; Nasir, Rohany; Yusooff, Fatimah (Faculty of Psychology, Universitas Surabaya, 2009)
The purpose of this quasi-experimental study was to determine the effectiveness of Cognitive Be- havioral Therapy Group Counseling in reducing employees’ work stress. Subjects for this study were 48 employees of Bank Mandiri Wilayah X, Makassar, Indonesia, selected by purposive sam- pling technique. The subjects were divided into three groups: weekly experimental group (E1), marathon experimental group (E2) and control group (K). Work stress scale adopted from Cooper’s Occupational Stress Indicator was used to measure stress. The data was analysed by t- test and ANCOVA. The results showed that both the weekly and the marathon groups counseling were effective in reducing work stress among the bank employees. Studi kuasi-eksperimental ini bertujuan menentukan keefektifan Konseling Kelompok dengan Terapi Perilakuan Kognitif dalam mengurangi stres kerja karyawan. Para subjek studi ini adalah 48 karyawan Bank Mandiri Wilayah X, Makassar, Indonesia, diseleksi melalui teknik sampling bertujuan. Para subjek dibagi ke dalam tiga kelompok: kelompok eksperimen mingguan (E1), kelompok eksperimen maraton (E2), dan kelompok kontrol (K). Skala stres kerja yang diadopsi dari Cooper’s Occupational Stress Indicator digunakan untuk mengukur stres. Data dianalisis dengan uji-t dan ANCOVA. Hasilnya menunjukkan bahwa kedua kelompok konseling, yang mingguan dan yang maraton efektif dalam mengurangi stres kerja di antara karyawan bank.